Implementasi Metode Design Thinking Dalam Aplikasi Giwang Sumsel - Iwan Mandala Putra; Dwi Rosa Indah (STMIK Budi Darma, 2023)
Giwang Sumsel is an application from the Culture and Tourism Office of South Sumatra Province that aims to provide information, facilitate tourism, and help tourists explore South Sumatra Province. The Giwang Sumsel application has many complaints from users, ranging from display problems to information conveyed that does not meet user desires. Usability evaluation testing needs to be done to determine the usefulness of the application for users. The research conducted usability evaluation testing using the system usability scale (SUS) method and then redesigned based on user needs using the design thinking method. Usability evaluation testing using the system usability scale (SUS) method has an assessment score of 1–5 with an average value of 68 to be categorized as a good design. The design thinking method was used during the process of redesigning the UI/UX design of the Giwang Sumsel application because at each stage it always involves users, so the hope is that the results will be the same according to the needs of users. At this stage, testing of the improved design will be carried out using the single ease question (SEQ) method, which has an assessment score of 1–7, and if the average value obtained is 55, the design can be categorized as a good design. The test results prove that the usability evaluation of the design before improvement with the design thinking method gets an average SUS value of 41.6, and the design results after improvement with the design thinking method get an average value of 69.9 with the single ease question (SEQ) method